Polymer-free viscoelastic fluid for improved oil recovery. (15th May 2021) - Chen, Changlong; Wang, Shuoshi; Harwell, Jeffrey H.; Shiau, Bor-Jier
Highlights: Oil-induced VES was identified within the Winsor III microemulsion domain. VES provides both ultralow o/w IFT and mobility control in oil displacement. Faster and greater tertiary oil recovery was achieved by oil-induced VES. VES can be made with high-salinity formation water without complex water treatment. Abstract: It has been observed that alkylpropoxy sulfates, sometimes called extended surfactants, exhibit an oil-induced viscoelastic behavior. This unique behavior occurs within the Winsor III microemulsion domain where the microemulsions are deemed "oil-starved", meaning that the oil content of the system is below the solubilizing capacity of the microemulsion. The resulting viscoelastic fluid offers dual benefits of producing both ultra-low oil/water interfacial tension (IFT) and favorable rheological characteristics such as serving as a displacing agent within the porous medium. In this work, the potential of the oil-induced viscoelastic formulations was explored in tertiary recovery application. First, the formulations were carefully tuned to achieve an ultralow IFT with the site-specific crude. Then only 4 – 6 vol% of crude oil or substitute paraffinic oil, was added with the freshly prepared aqueous solution to trigger the desired rheological behavior. The resulting fluid was then injected to the porous medium. Based on the results of 1-D glass column and 2-D Hele–Shaw cell studies, smoothly advancing of oil banks were realized shortly after injection of the viscoelastic fluids, which in turn led to fast oil breakthrough, high oil cut, and better tertiary recovery. Significant advantages of the developed viscoelastic systems are that they offer a robust system with versatile polymer-free injection package and the potential for field tertiary recovery involving a single-slug that drastically improves the volumetric sweep efficiency and the microscopic displacement efficiency, without the complex water treatment system and polymer mixing system required for surfactant-polymer (SP) or alkaline- surfactant-polymer (ASP) floods.